Bibliometric analysis and visualization of the extrahepatic portal venous obstruction publication landscape - Anjan Kumar Dhua; Mohit Garg; Devendra Kumar Yadav; Prabudh Goel; Vishesh Jain; Sachit Anand; Ajay Verma (Wolters Kluwer Medknow Publications, 2023)
Introduction: A scientometric analysis was conducted to characterize the global research publications in extrahepatic portal venous obstruction (EHPVO), and state-of-the-art visualization graphics were generated to provide insight into specific bibliometric variables. Materials and Methods: The Web of Science database was accessed for research productivity and bibliometric variables of countries, institutions, authors, journals, and content analysis of top-20 cited documents were performed. Collaborative networks and co-occurrence of keywords map were generated using VOSviewer software. Results: Two hundred and sixteen records were retrieved with an annual growth rate of 2.53%. India is the leading country in productivity (n = 4339), followed by the USA and China. Post Graduate Institute of Medical Education and Research, Chandigarh, was the top productive institute. Sarin SK was the most prolific author, having the highest citations received and h-index. The hotspot topics were "portal hypertension," "cirrhosis," "children," "biliopathy/cholangiopathy," "liver fibrosis," and "liver transplantation" as per keyword co-occurrence networking. J Gastroenterol Hepatol had the most publications of EHPVO research as well the h-index. Regarding collaborative network mapping, the USA and Primignani M were the significant nodes among country and author, respectively. Conclusion: EHPVO research publication volume is low but is gradually progressing with dominant contributions from Indian institutes and authors. Most highly cited articles are of low level of evidence, and multi-institutional collaborative research can be the way forward.